Is there a correlation between an eGFR slope measured over a 5-year period and incident cardiovascular events in the following 5 years among a Flemish general practice population: a retrospective cohort study. Issue 11 (12th November 2018) - Van Pottelbergh, Gijs; Mamouris, Pavlos; Opdeweegh, Nele; Vaes, Bert; Goderis, Geert; Van Den Akker, Marjan
Abstract : Objectives: To examine if the estimated glomerular filtration rate (eGFR) slope over a 5-year period is related to incident cardiovascular (CV) events in the following 5 years. Design: Retrospective cohort study. Setting: Primary care. Participants: All patients aged ≥50 years with at least four eGFR measurements between 01 January 2006 and 31 December 2010 were included in the study. Outcome measures: During the follow-up period (01 January 2011 until 31 December 2015), CV events (acute myocardial infarction, stroke (cerebrovascular accident (CVA)/transient ischemic attack (TIA)), peripheral arterial disease and acute heart failure) were identified. Methods: The slope was calculated by the least square method (in mL/min/year). The following slope categories were considered: (−1 to 1), (−3 to −1) (−5 to −3), ≤−5, (1 to 3), (3 to 5) and ≥5.00 mL/min/year. Cox proportional hazards model was used to assess the association between eGFR slope and incidence of CV events. Survival probability from CV events was estimated per slope category. Results: 19 567 patients had at least four eGFR measurements, of whom 52% was female. 12% of the ≤−5 slope category developed a new CV event in comparison to 7.8% of the reference group and 5.4% of the ≥5 slope category. Survival rates were worst in those with a slope ≤−5. Patients with a slope of (−5 to −3) and ≤−5 had an adjusted HR of 1.37 and 1.55, respectively. Most patients with a slope <−3 mL/min had an eGFR still >60 mL/min. Conclusions: Negative eGFR slopes of at least 3 mL/min/year give irrespectively of the eGFR itself a higher risk of CV events compared with patient groups with stable or improved kidney function. So the eGFR slope identifies an easy to define group of patients with a high risk for developing CV events.